1961
DOI: 10.1182/blood.v17.3.267.267
|View full text |Cite
|
Sign up to set email alerts
|

Platelet and Fibrinogen Survival in Normal and Abnormal States of Coagulation

Abstract: 1. Platelet and fibrinogen survival have been studied by isotope tagging in normal and abnormal states of coagulation in humans and dogs. 2. By our technic, the normal curve of platelet survival is exponential. Evidence is given that such a curve is obtained because of random utilization of the platelets in the continuous process of coagulation. 3. In the postoperative subject and in the subject receiving epinephrine injections, platelet survival is shortened because the process o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0
1

Year Published

1962
1962
2004
2004

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(11 citation statements)
references
References 6 publications
1
9
0
1
Order By: Relevance
“…Thus, in states characterized by alterations in the rate of formation or activation of thromboplastin or thromboplastin precursors the normal reticuloendothelial system is competent to remove the proeoagulant substance and prevent thrombin formation and conversion of fibrinogen to fibrin. In this regard, Adelson and associates (28) have demonstrated that hypercoagulable states accompanying thrombus formation, operative procedures, and epinephrine injection considerably modify the half-life of labeled platelets but have no effect on the rate of utilization of labeled fibrinogen.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in states characterized by alterations in the rate of formation or activation of thromboplastin or thromboplastin precursors the normal reticuloendothelial system is competent to remove the proeoagulant substance and prevent thrombin formation and conversion of fibrinogen to fibrin. In this regard, Adelson and associates (28) have demonstrated that hypercoagulable states accompanying thrombus formation, operative procedures, and epinephrine injection considerably modify the half-life of labeled platelets but have no effect on the rate of utilization of labeled fibrinogen.…”
Section: Discussionmentioning
confidence: 99%
“…The survival time of isotopically labelled platelets has by most authors been expressed as platelet half-life time (TYz), or as the time of disappearance of labelled platelets from the circulation (Adelson et al 1961, Davey & Lander 1964, O'Neill & Firkin 1964, Najean et al 1967, Abrahamsen 1968a, Kotilainen 1969, Murphy & Gardner 1969.…”
mentioning
confidence: 99%
“…Other investigators have prescnted evidence that adrenaline may accelerate blood coagulation by increasing the activity of clotting components such as Factor VIII (Ingrain, 1961). Adrcnaline increases the platelet count and this increase may be sustained over a pcriod of weeks in rabbits givcn daily injections (Ozge and Mustard, 1962) ; we and others have also found that it can shorten platelet survival and increase platelet turnover (Adelson et a/., 1961 ;Ozgc and Mustard, 1962). Thus three competing views on thc site of action of adrenaline on thrombosis can be considcrcd at this stagc: first, rhe artcrial wall; secondly, clotting factors; and thirdly, the…”
Section: Discussionmentioning
confidence: 75%